PERBANDINGAN EFEK H2SO4 DAN ZAT PENGATUR TUMBUH CAMPURAN DARI BAHAN ALAMI DALAM MEMATAHKAN DORMANSI BENIH KOPI ROBUSTA - Nurhayati Nurhayati; Anto Susanto (Journal of Agro Plantation (JAP), 2026)
Coffee seeds often undergo dormancy, which hinders the germination process. The use of natural plant growth regulators (PGRs) such as a mixture of young coconut water and red onion extract can be an alternative to break dormancy, as the ingredients are easily obtained, safe, and environmentally friendly. This study aims to determine the optimal concentration of the GHR mixture that can replace the use of H₂SO₄ on Robusta coffee seeds. The research was conducted at the Experimental Farm on Jl. Gusti Mesir, Medan Jaya Village, Kayong Utara, from January to April 2025, using a completely randomized design with six treatments and three replications, each with 25 seeds per replication. The treatments consisted of 20% H₂SO₄ (control), PGRs mixtures at concentrations of 20%, 40%, 60%, 80%, and 100%. Parameters observed were germination percentage, germination rate, vigor index, and dormancy intensity. Data analysis used analysis of variance and BNT test at the 5% level. The results showed that the 100% PGRs mixture could replace H₂SO₄ in breaking seed dormancy especially robusta coffee seed.